Performance evaluation and efficiency enhancement of a space thermionic fuel element for thermal energy conversion and utilization. (5th June 2020) - Deng, Yangbin; Qiu, Bowen; Lu, Kailin; Yin, Yuan; Gong, Xing; Pang, Bo; Huang, Xi; Li, Yongchun; Wu, Yingwei; Su, Guanghui
Highlights: Thermionic conversion and electric circuit models were developed for TFEs. Coupled with FROBA-SPACE, a simulation code was developed and validated. Strategy study on energy efficiency enhancement of TOPAZ-II was conducted. Conversion efficiency was promoted from 10% to over 15%. Utilization efficiency was increased from 6% to over 8.5%. Abstract: Efficiency enhancement of thermal energy conversion and utilization is one of the critical issues in space exploitation and exploration. With the full consideration of material characteristics, space charge effect and Joule dissipation, thermionic conversion models were established based on Richardson's law. The models were coupled with a thermo-mechanical simulation code, developing the comprehensive simulation capability of the whole thermionic power system for the first time. This tool was validated by experiment data, and then used to conduct a parametric study for a space nuclear reactor named TOPAZ-II. The parametric study figured out key operating features and influencing factors of thermionic conversion. Based on the parametric study, the optimization for utilization efficiency enhancement was undertaken from the view of thermionic conversion performance improvement, electric circuit design optimization and radiation loss reduction. It was found that the conversion efficiency could be promoted from about 10% to over 15% and the utilization efficiency was increased from about 6% to over 8.5% by use of innovative materials or geometry designs, while ensure thermal parameters within the normal operating range. However, results also indicate that some efficiency enhancement strategies proposed without the consideration of the whole system in previous studies might to be useless.